(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the artistic and philosophical meanings of ideas in the stories of modern writers, in particular, the disclosure of the hero‘s psyche and the plot system using natural phenomena. In particular, the wind was studied from the point of view of the fact that it can penetrate into all times and places, can arise anywhere, can take various forms - from a pleasant breeze to a terrible hurricane, and can serve any purpose of the author, embodying the characteristics of negativity and positivity.